How do unusual working schedules affect social life? - Juliane Scheffel (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
The widening of the working hour distribution complicates the coordination of social leisure. This paper examines the short- and long-run impact of unusual working schedules on social life using German Time Use Data for 2001/02. I find evidence that younger workers with higher than median earnings seem to accept higher levels of solitary leisure as investment and because of the substantial wage premia. Younger workers tend to substitute sleep with free time. Older workers, in contrast, tend to sleep less which can be interpreted as elevated risk of mental and physical health.
Keywords: J22; J28; J81; D62; 330; shift work; non-standard working hours; time allocation; social capital; social life; solitary leisure; adverse consequences; Schichtarbeit; Soziale Beziehungen; Zeitverwendung; Freizeitverhalten; Junge Arbeitskräfte; Ältere Arbeitskräfte; Deutschland